Evaluating the Associations Between Exposure to Tobacco Interventions During Inpatient Treatment and Substance Use Outcomes: Findings From a Natural Experiment. Issue 3 (May 2021) - Romano, Isabella; Costello, Mary Jean; Sousa, Sarah; Li, Yao; Bruce, Dominique; Roth, Don; MacKillop, James; Rush, Brian
Abstract : Objective: In this study, we took advantage of a natural experiment that occurred within a substance use disorders (SUD) treatment setting which first saw the implementation of an evidence-based practice (EBP) for tobacco cessation, followed by the implementation of a tobacco-free policy (TFP) that included a campus-wide tobacco ban. We sought to examine how implementation of the EBP and TFP was associated with substances use outcomes, in addition to tobacco use, up to 3-months posttreatment. Methods: Data were collected from patients in a substance use disorders treatment program at baseline, discharge, 1-, and 3-months posttreatment. Using a quasi-experimental design and generalized estimating equations, we modelled how patients' (N = 480) exposure to one of 3 interventions (1: treatment as usual [TAU], 2: EBP, and 3: EBP + TFP) was associated with overall abstinence from tobacco, alcohol, and other substances over time. Measures of tobacco use frequency, amount, and quit attempts were also modelled among a sub-sample of participants who self-reported using tobacco before treatment. Result: Exposure to the EBP + TFP was associated with increased tobacco abstinence (odds ratio [OR] = 1.93, 95% confidence interval [CI] [1.29, 2.90]) over time, including decreases in tobacco use frequency (OR = 0.78, 95% CI [0.68, 0.89]) and amount (OR = 0.80, 95% CI [0.67, 0.96]), and increased in likelihood of making a quit attempt (OR = 1.75, 95% CI [1.10, 2.80]) compared to TAU. Exposure was not associated with alcohol and/or other substance use. Conclusions: Comprehensive tobacco interventions that include EBP + TFP can promote tobacco cessation and reduced tobacco use following inpatient SUD treatment, without adversely affecting the use of other substances. Abstract : Supplemental Digital Content is available in the text